PENGARUH KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN KEPUTUSAN INVESTASI SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2024) - Laura Januari; Mahatma Kufepaksi (Nusantara Hasana Journal, 2026)
This study aims to examine and analyze the effect of debt policy and dividend policy on firm value with investment decisions as a moderating variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2024 period. Using the purposive sampling method, a sample of 46 companies was obtained with a total of 322 observations, which were analyzed using Panel Data Regression Analysis with the Moderated Regression Analysis (MRA) approach using E-Views 13. The results showed that debt policy has a significant negative effect, while dividend policy has a significant positive effect on firm value. Furthermore, investment decisions are proven to moderate by strengthening the effect of debt policy on firm value, but weakening the effect of dividend policy on firm value. Meanwhile, the control variable firm size has a significant negative effect, whereas firm age has no significant effect on firm value.